Peroral endoscopic myotomy (POEM) for complex achalasia and the POEM difficulty score. Issue 2 (3rd February 2019) - Bechara, Robert; Woo, Matthew; Hookey, Lawrence; Chung, Wiley; Grimes, Kevin; Ikeda, Haruo; Onimaru, Manabu; Sumi, Kazuya; Nakamura, Jun; Hata, Yoshitaka; Maruyama, Shota; Gomi, Kuniyo; et al.
Abstract : Background: Peroral endoscopic myotomy (POEM) for achalasia is technically challenging to carry out in patients with type III, multiple prior treatments, prior myotomy, and sigmoid type. Herein, we present a series of consecutive patients with complex achalasia and introduce the POEM difficulty score (PDS). Aim: To demonstrate the application and discuss the utility of PDS and present the feasibility, safety, and efficacy of POEM in complex achalasia patients. Methods: Forty consecutive POEM were carried out with 28 meeting the criteria for complex achalasia. Primary outcome was clinical success (Eckardt score ≤3) at a minimum of 3 months follow‐up. Secondary outcomes included adverse events, procedural velocity and PDS. Results: Twenty‐eight complex and 12 non‐complex POEM procedures were carried out with 100% and 92% clinical success, respectively, without any major adverse events with a median follow up of 15 months (complex) and 8 months (non‐complex). Mean velocities for non‐complex, type III, prior myotomy, ≥4 procedures and sigmoid type were as follows: 4.4 ± 1.6, 4.8 ± 1.5, 5.9 ± 2.2, 6.9 ± 2.2 and 8.2 ± 3.2 min/cm, respectively. Median PDS for non‐complex, type III, prior myotomy, ≥4 treatments and sigmoid type were 1 (0–3), 2 (0–4), 2.5 (1–6), 3 (2–6) and 3.5 (1–6), respectively. PDS was shown to correlate well with procedural velocity with a correlation coefficient of 0.772 (Spearman's P < 0.001). Conclusions: PDS identifies the factors that contribute to challenging POEM procedures and correlates well with procedural velocity. The order of increasing difficulty of POEM in complex achalasia appears to be type III, prior myotomy, ≥4 treatments and sigmoid type.